The Criminalization of Sexual Violence Victims: A Normative Evaluation Through the Lens of Sociology of Law - Ericha Chelsea Oktaviani (Universitas Negeri Yogyakarta, 2026)
This study examines the phenomenon of the criminalization of sexual violence victims by utilizing the sociology of law as a normative-analytical tool. Despite progressive legal reforms, victims are frequently counter-reported and criminalized, revealing a significant gap between statutory protection and judicial reality. Adopting a qualitative research design with a normative-evaluative approach, this research analyzes how formal legal norms fail to articulate the real-world experiences, behaviors, and perceptions of victims within the legal realm. The results indicate that the criminalization of victims is deeply rooted in structural and cultural biases embedded within law enforcement practices, which often prioritize rigid legal-formalistic interpretations over victim-centric justice. By using the sociology of law as an analytical lens, this study demonstrates that legal effectiveness cannot be achieved if statutory norms are applied in isolation from gender-sensitive social realities. Consequently, this research recommends a comprehensive evaluation of procedural laws and calls for institutional reforms to ensure that secondary victimization is mitigated and that judicial decision-makers internalize the sociological substance of protective laws.